Global stability of a diffusive predator–prey model with discontinuous harvesting policy. (November 2020) - Zhang, Xuebing; Zhao, Hongyong
Abstract: We investigate a diffusive predator–prey system with discontinuous harvesting function under Neumann boundary conditions. Then the existence and some estimates of the positive solution of the system are acquired. Based on the differential inclusions theory, we discuss the existence of constant equilibrium. Finally, by constructing a suitable Lyapunov functional, we study the global asymptotic stability of the positive equilibrium.